2015
DOI: 10.1161/hypertensionaha.115.05333
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Participate in Neurogenic Regulation of Hypertension

Abstract: Hypertension is associated with neuroinflammation and increased sympathetic tone. Interference with neuroinflammation by an anti-inflammatory reagent or overexpression of interleukin-10 in the brain was found to attenuate hypertension. However, the cellular mechanism of neuroinflammation, as well as its impact on neurogenic regulation of blood pressure, is unclear. Here, we found that hypertension, induced by either angiotensin II or L-NG-nitro-l-arginine methyl ester, is accompanied by microglial activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 28 publications
9
105
0
1
Order By: Relevance
“…These studies showed changes in microglial morphology (enlarged soma, process retraction) and increased production of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) [16][17][18]. Our results confirm that pressive Ang II leads to cerebral gliosis and extends this finding to another brain region, namely the hippocampus.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These studies showed changes in microglial morphology (enlarged soma, process retraction) and increased production of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) [16][17][18]. Our results confirm that pressive Ang II leads to cerebral gliosis and extends this finding to another brain region, namely the hippocampus.…”
Section: Discussionsupporting
confidence: 85%
“…We decided to examine TNF-α in more detail rather than IL-6, based on previous evidence that hypothalamic microglia isolated from Ang II-treated mice exhibit a significant increase in TNF-α expression and a milder increase in IL-6 [17,18]. In line with the proposed hypothesis, ELISA analysis of hippocampal homogenates revealed a significant increase in TNF-α levels in mice infused with Ang II 1000 ng/kg/min compared to controls (p = 0.040, Fig.…”
Section: Effect Of Ang II On Tnf-α Production In the Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide further evidence that they do not. Because it has recently been discovered that microglia mediate neurogenic hypertension and that their depletion leads to significantly attenuated blood pressure (36), the triggering of microglia apoptosis could be an unidentified reason why nimodipine treatment is highly effective in hypertension. In addition to the apoptosis-inducing effect, we obtained evidence that nimodipine modulates the proinflammatory activity of surviving microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both M1 (MHC II, CCR7, interferon-γ receptor, and iNOS) and M2 markers (CD36, mannose receptor, Tie2, and IL-4 receptor α) were upregulated in microglia from hypertensive mice, but not in monocytes, which may be explained by the neurogenic regulation of hypertension [232]. Other studies demonstrated that proinflammatory M1 macrophages are predominant in the aortas stimulated by angiotensin-II for 7 days [233,234]; however, prolonged infusion of angiotensin-II for 14 to 28 days recruited Ly-6C hi monocytes that differentiated into M2 macrophages [235].…”
Section: Hypertensionmentioning
confidence: 92%